Envolvimento de receptores canabinoides na sensibilização e preferência condicionada ao lugar induzidas por cocaína - Jadna Bogado Lopes (2017)
Drugs of abuse, such as cocaine, induce a reward effect and facilitate dopaminergic neurotransmission on the mesolimbic pathway. The endocannabinoid system, represented by cannabinoid receptors (CB1 e CB2), endocannabinoids and enzymes responsible for their synthesis and degradation, modulates the neurotransmission pathway and can be an important pharmacological target for the treatment of addiction. Herein, we tested the hypothesis that cannabinoid receptors are implicated on motor sensitization effects, conditioned place preference (CPP) and hippocampal neuronial activation induced by cocaine. Swiss male mice received AM251 (CB1 receptor antagonist) or JWH133 (CB2 receptor agonist) injections during acquisition or expression phases of the above mentioned behavioural tasks. AM251 inhibited sensitization, when administered during the acquisition (0,3, 1 and 3 mg/kg) or expression. (1 and 3 mg/kg) phases, and CPP, when administered during acquisition phase (10 mg/kg). JWH133 did not prevent the acute cocaine-effect. However, it attenuated sensitization when administered during acquisition (0,3 and 1 mg/kg) or expression (1 and 3 mg/kg) phases. Moreover, administration of JWH133 (10 mg/kg) prevented cocaine-induced CPP on both phases. JWH133 effects were reverted by AM630 (CB2 receptor antagonist) administration. The attenuation of the cocaine-induced contextual memory occurred along with a decrease on neuronal activation (c-Fos positive cells) on the hippocampus of animals treated with AM251 and JWH133. Therefore, behavioural and cellular effects induced by cocaine seem to be mediated by activation of CB1 receptor and inhibited by activation of CB2 receptor. As both receptors are Gi/o coupled receptors, we speculate that they act on different neuronal types, with CB1 e CB2 localized on GABAergic and dopaminergic neurons, respectively.